PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK BERKEBUTUHAN KHUSUS DI SLBN 2 PADANG (STUDI ATAS SISWA TUNAGRAHITA) - Ummah, Kuntum Khaira; Nurmaliah, Yayah; Khadijah, Siti (Dharmas Education Journal (DE_Journal), 2023)
Mentally retarded children are a classification of children with special needs who have cognitive deficiencies because mentally retarded children only have an IQ of approximately 30-70. The shortcomings possessed by mentally retarded children become a basis for parents, teachers and people around them so that they receive opportunities and proper treatment from their environment as received by normal individuals. This research was carried out at SLBN 2 Padang because this school is one of the Special Schools (SLB) which has the largest number of mentally retarded students in Padang. The problems explored in this research are the lesson plans used by PAI teachers in learning, the PAI learning process for mentally retarded children, evaluation of PAI learning for mentally retarded children, inhibiting and supporting factors in PAI learning for mentally retarded children at SLBN 2 Padang. This research uses a qualitative approach aimed at describing, analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually and in groups. The results of the research show that the lesson plans used by PAI teachers in terms of format are the same as those used in normal schools, however the KI, KD and indicators have been lowered according to the abilities of mentally retarded children, in the learning process there are differences with children in normal schools even though they have not been implemented optimally. The evaluation carried out is also different from normal children, but it is very unfortunate that PAI teachers at SLBN 2 Padang do not carry out mid-term assessments (PTS).